Studi Skenario Kendali Load Shedding Sistem Tenaga Listrik PT Chandra Asri Petrochemical Tbk - Ceri Ahendyarti; Donny Prakarsa Utama (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2022)
PT Chandra Asri Petrochemical Tbk's (CAP) electric power system uses 3 types of power lines, namely, PLN, GTG (Gas Turbine Generator) and STG (Steam Turbine Generator) lines. Disturbances in the electrical power system can occur either small disturbances or large disturbances (blackout). One of the optimization strategies and protection systems to avoid disturbances and maintain the stability of the electric power system is by means of load shedding. Load Shedding is carried out using a Quantum Modicon Schneider PLC with Magelis HMI display on the ISP (Interconnection Synchro Panel) or panels connected to each generator. With some disturbances that caused some losses to the Company PT Chandra Asri Tbk. mentioned above, it is offered to solve the problem by providing a variety of load shedding scenarios. In this study, a simulation of the calculation and variation of load shedding was carried out. Keywords: load shedding, PLC, HMI